Design and evaluation of two-layer roller compacted concrete - Mohammed, Haneen Adil (2018)
Roller Compacted Concrete (RCC) is a mixture of well graded aggregates, cement and water. It is placed with a high compaction asphalt type paver and compacted to high density by vibratory rollers to provide a high strength and durable pavement structure. RCC requires no formwork, surface finishing, dowelled joints or reinforcement. These characteristics make RCC simple, fast and economical. However, it also presents difficulties with high-speed applications related to surface texture and surface evenness. These difficulties have so far restricted the use of RCC to the lower layers of normal roads.